Monothermal Caloric Screening to Improve Healthcare Value. Issue 3 (May 2016) - Thatcher, Aaron L.; Beckerman, Margot L.; Telian, Steven A.; King, William Michael
Abstract : Objectives: To evaluate whether monothermal caloric screening can reduce the number of caloric irrigations required in the vestibular testing battery while maintaining diagnostic accuracy. Design: Prospective controlled cohort study. Three hundred and ninety patients referred for vestibular testing at this tertiary referral health system over a 1-year period were evaluated; 24 patients met exclusion or failure criteria and 366 patients were included in the study. Population was 35.6% male; average age was 50.4 years old. Each patient underwent caloric testing using either warm or cool water irrigation initially and this data was used for monothermal screening data. All patients then completed bithermal binaural caloric testing to obtain the "gold standard" bithermal data for comparison. The sensitivity and specificity of monothermal cool or monothermal warm caloric tests were calculated using a receiver operating characteristic curve analysis. Results: Using a monothermal interear difference threshold of 25%, warm monothermal screening had sensitivity of 98.0%, specificity of 91.3%, false negative rate of 2%, and false positive rate of 8.7%. Cool monothermal screening also had excellent sensitivity (92.3%) and specificity (95.3)%, with a false negative rate of 7.7%, and a false positive rate of 4.7%. The diagnosis associated with the single false negative warm monothermal caloric test was compensated vestibular paresis. In the study population, 71.9% had a negative monothermal screen; if the monothermal data were accepted, 2 fewer irrigations would have been performed resulting in an average saving of $264 (typical Medicare reimbursement for 2 irrigations) billed per patient screened as well as shortening the average testing battery by about 15 min. Conclusions: Warm monothermal caloric screening can reduce time and cost of vestibular testing while nearly matching the diagnostic accuracy of bithermal testing. Abstract : This is a prospective study to determine the diagnostic efficacy of monothermal caloric screening for vestibular weakness in a tertiary care center. Patients were tested using either warm or cool water irrigations to obtain monothermal data, after which they completed bithermal testing. A receiver operating characteristic (ROC) analysis was used to determine the sensitivity and specificity of the monothermal screening test relative to the bithermal control data. Warm and cool monothermal tests had sensitivities of 98.0% and 92.3%, respectively, and specificities of 91.3% and 95.3%, respectively. The data show that monothermal caloric screening can be nearly as effective as bithermal screening.